The Mediating Role of Financial Performance in the Impact of Corporate Governance on the Market Share in the Iraqi Listed Companies - Khudhair, Ahmed Hakim; Fakhari, Hossein (Journal of Ecohumanism, 2025)
This study examines how financial performance moderates the effect of corporate governance on the market share of Iraqi companies. The study examines companies found on the iraqi Stock Exchange employing multiple regression and panel data analysis over 2012-2022. After the data were systematically removed, 33 companies were selected from 130. The study reveals that corporate governance positively impacts market share, and financial performance moderating this relationship. The findings suggest that Financial performance could indefintely intermediate the impact of good corporate governance proxied by corporate secretary on Market Share, and it ultimately could be determined that the corporate secretary has an indirect effect on the Market Share through financial performance. The study highlights. The research underscores the significant impact of corporate governance on market power and financial performance, while also emphasizing several important implications for management. Corporate governance has a crucial part in boosting brand reputation and market positioning. Evidence suggests that organizations that are dedicated to implementing strong corporate governance practices are able to positively influence consumer perceptions, thereby expanding their customer base. The alignment of strategic initiatives enhances market power and establishes a sustainable competitive advantage.